People Management in the Development Training Process in Organizations / Gestão de Pessoas no Processo de Treinamento para Desenvolvimento nas Organizações - Duarte, Rhayana Claudyelle Carneiro; Loiola, Edney; Viana, Diego Carvalho (ID on line. Revista de psicologia, 2020)
The importance of training and development in organizations points out the main deficiencies that can occur with the lack of them, for the employee. The main objective of this literature review is to analyze the relevance of the training opportunity for improvements to employees and organizational development. Training permeates valuation and guarantees development within the company by resulting in motivation among them, generating a differential in the quality of the product or service in the market in which it operates.